KEMAMPUAN KOMUNIKASI CALON GURU UNTUK MEMBANGUN KEMAMPUAN PENALARAN SISWA - Kurniawan, Dian; Muzdalipah, Ipah (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
This study aims to describe the communication skills of prospective teachers in learning mathematics to build students' reasoning abilities. The research was carried out in class X SMAN 1 Lawang with 38 students and SMAN 1 Singosari with 40 students. The subjects of this research were KPL students from the Mathematics Education Study Program, State University of Malang, consisting of 2 students. Mathematics learning for prospective teachers is Graph material and Quadratic Functions. This research is a descriptive qualitative research. The instruments in this study were interviews, field notes, and video recordings. The results of this study are that prospective teachers are able to communicate theorems and procedures well, according to the concept map material on Graphs and Quadratic Functions. Functions can be demonstrated through writing and geometric shapes by using mathematical interpretations from real life, performing calculations and predictions, explaining reasons why an answer can be accepted as a truth, finding an answer so as to be able to reveal connections and provide insight into the underlying mathematical structure. The exposition activities of prospective teachers through generalization activities of proof - proving the problems given help students get a truth, so that in this case the prospective teachers have succeeded in building students' reasoning. Errors that occur from a small number of students when making conclusions are expected to be minimized through a deeper study of mathematical communication to build student reasoning.Keywords: Teacher candidates, Mathematical Communication, Student Reasoning